2019
DOI: 10.1021/acs.chemrev.8b00514
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbenes in Materials Chemistry

Abstract: N-Heterocyclic carbenes (NHCs) have become one of the most widely studied class of ligands in molecular chemistry and have found applications in fields as varied as catalysis, the stabilization of reactive molecular fragments, and biochemistry. More recently, NHCs have found applications in materials chemistry and have allowed for the functionalization of surfaces, polymers, nanoparticles, and discrete, well-defined clusters. In this review, we provide an in-depth look at recent advances in the use of NHCs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
342
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(353 citation statements)
references
References 473 publications
7
342
0
4
Order By: Relevance
“…The interest of these helicenic organometallic derivatives originates from the association of the inherent properties of the helicene with those of the transition metals (controlled coordination geometry, redox activity, strong spin‐orbit coupling, strong emission and absorption, reactivity), giving access to original chiral multifunctional molecules. During the last two decades, organometallic complexes based on N ‐heterocyclic carbenes (NHCs) have experienced a boom due to their important applications in catalysis, in medicinal chemistry, and in molecular materials . For these reasons, we have been recently investigating the development of molecular architectures associating helicenes, NHCs, and organometallic chemistry, in order to develop a new family of chiral complexes, namely, organometallic NHC‐helicene complexes (see Figure , A ‐ C ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest of these helicenic organometallic derivatives originates from the association of the inherent properties of the helicene with those of the transition metals (controlled coordination geometry, redox activity, strong spin‐orbit coupling, strong emission and absorption, reactivity), giving access to original chiral multifunctional molecules. During the last two decades, organometallic complexes based on N ‐heterocyclic carbenes (NHCs) have experienced a boom due to their important applications in catalysis, in medicinal chemistry, and in molecular materials . For these reasons, we have been recently investigating the development of molecular architectures associating helicenes, NHCs, and organometallic chemistry, in order to develop a new family of chiral complexes, namely, organometallic NHC‐helicene complexes (see Figure , A ‐ C ) .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structures of formerly reported iridium complexes coordinated to NHCs bearing a ( A ) [6]helicene, ( B ) [5]helicene, and ( C ) [4]helicene unit, respectively. Chemical structures of the novel iridium complexes 1a,b and rhodium complex 1′a reported herein…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N‐Heterocyclic carbenes (NHCs), are utilized widely as supporting ligands on transition metal ions to produce molecules and materials useful in a range of applications . They are strongly σ‐donating and comparatively weakly π‐accepting ligands, and in general form stronger bonds with metals compared to phosphines .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Although al arge number of ligated atomically precise Au NCs have been successfully attained in recent decades by employing organic ligands,i ncluding phosphines, [5] thiols, [6] and alkynyls, [7] quite limited success has been achieved to demonstrate the direct use of the ligated atomically precise Au NCs as atruly homogeneous catalyst in liquid-phase reactions without being loaded on supports. [9] Several groups have demonstrated that NHCs readily form ar obust self-assembled monolayer on ac oinage metal surface and function as ap erformance-enhancing modifier. [9] Several groups have demonstrated that NHCs readily form ar obust self-assembled monolayer on ac oinage metal surface and function as ap erformance-enhancing modifier.…”
Section: Introductionmentioning
confidence: 99%